PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA (Studi Kasus Pada Kampus Pariwisata X di Jakarta) - Soerjanto (LPPM and Travel Operation Department Universitas Asa Indonesia, 2018)
This study aims to analyze the influence of transformational leadership and motivation on employees’ performance through job satisfaction (a case study in X Tourism Academy). Respondents of this study include 52 employees of X Tourism Academy. The sampling is saturation sampling, and the analysis is Path Analysis. Results of the study show that transformational leadership has positive and significant influences on employees’ performance. Transformational leadership indirectly influences employees’ performance through job satisfaction. Motivation has positive and direct influence on employees’ performance. Motivation indirectly and positively influences employees performance through job satisfaction. Job satisfaction positively and significantly influences employees’ performance. The direct influences of transformational leadership and motivation on employees’ performance are greater than those of indirect influences through job satisfaction. This suggests that job satisfaction is not an intervening variable for transformational leadership and motivation on employees’ performance in X Tourism Academy, Jakarta.